Perancangan Aplikasi Forcasting Penjualan Mobil Isuzu Metode Trend Moment PT. Astra Isuzu Cab. Medan - Nur Ahmad Indaka; Garuda Ginting (STMIK Budi Darma, 2022)
An understanding of forecasting is the basis for how companies plan and predict sales volumes and commodity goods to be sold. This can be seen from the company's analysis of the quality of goods and the quantity of goods that have high purchasing power. We cannot deny that forecasting applications can help in solving this problem. In the forecasting application and application of the trend moment method in this study for analyzing car sales at PT.Astra International Tbk_Isuzu web-based it really helps companies in analyzing forecasting for 2020, the results show Trend (Y) = 6134.389, Season Index = 1.0274 and value The APE is 32.016%, while for forecasting data for 2021 the results are Trend (Y) = 1866.101, Seasonal Index = 1.094 and the APE value is 89.585%. There is a significant difference in forecasting data for 2020 and 2021 from PT. Astra International Tbk_Isuzu car sales, this affects the value of car sales and the decreased power of customer demand in choosing the type of Isuzu car.